Flavanones from the flower of Macaranga triloba - Zakaria, Ishak; Ahmat, Norizan; Ahmad, Rohaya; Mohd Jaafar, Faridahanim; Ab. Ghani, Nurunajah; Khamis, Shamsul (IDOSI Publications, 2010)
Macaranga triloba belongs to the family of Euphorbiaceae. Investigation on the dichloromethane extract of flower of Macaranga triloba collected at Hulu Terengganu, Malaysia has yielded four flavanone compounds known as 6-prenyl-3’-methoxy-eriodictyol (1), nymphaeol-B (2), nymphaeol-C (3) and 6-farnesyl3’,4’,5,7-tetrahydroxyflavanone (4). The structures of these compounds were elucidated based on spectroscopic methods including nuclear magnetic resonance (NMR-1D and 2D), UV, IR as well as mass spectrometry. This is the first report of 6-prenyl-3’-methoxy-eriodictyol(1) and 6-farnesyl-3’,4’,5,7-tetrahydroxyflavanone (4) from the genus of Macaranga.